ACSL4 reprograms fatty acid metabolism in hepatocellular carcinoma via c-Myc/SREBP1 pathway. (1st April 2021) - Chen, Junru; Ding, Chaofeng; Chen, Yunhao; Hu, Wendi; Yu, Chengkuan; Peng, Chuanhui; Feng, Xiaode; Cheng, Qiyang; Wu, Wenxuan; Lu, Yuejie; Xie, Haiyang; Zhou, Lin; et al.
Abstract: Lipid metabolic reprogramming plays a pivotal role in hepatocellular carcinoma (HCC) development, but the underlying mechanisms are incompletely characterized. Long chain acyl CoA synthetase 4 (ACSL4), a member of acyl-CoA synthetases (ACS) family, has been identified as a novel marker of alpha-fetoprotein-high subtype HCC and as an oncogene. Here, we identified a new function of ACSL4 in HCC lipid metabolism. ACSL4 can modulate de novo lipogenesis by accumulating intracellular triglycerides, cholesterols, and lipid droplets in HCC. Mechanistically, ACSL4 upregulates the master lipogenesis regulator sterol regulatory element binding protein 1 (SREBP1) and its downstream lipogenic enzymes in HCC cells via c-Myc. Moreover, SREBP1 is crucial for ACSL4-mediated regulation of lipogenesis as well as HCC cell proliferation and metastasis, as SREBP1 overexpression rescues lipogenic deficiency and decreased oncogenic capabilities associated with ACSL4 suppression in vitro and in vivo . Clinically, our data showed that the expression of ACSL4 was positively correlated with that of SREBP1 in HCC patients, and the combinational biomarkers showed strong predictive value for HCC. Together, our findings uncover a new mechanism by which ACSL4 modulates aberrant lipid metabolism and promotes the progression of HCC. Highlights: ACSL4 modulates de novo lipogenesis in HCC. ACSL4 mediates aberrant lipid metabolism through upregulating lipogenic enzymes. ACSL4 enhances the expression of lipogenic enzymes via c-Myc/SREBP1 cascade. SREBP1 is crucial for ACSL4-mediated regulation of lipogenesis as well as HCC cell proliferation and metastasis . ACSL4 and SREBP1 are positively correlated and the combinational biomarkers showed strong predictive value for HCC.